(untitled) (Current Horticulture, 2024)
An experiment was conducted to standardized dehydration techniques for cluster bean (Cyamopsis tetragonoloba L.) pods at ICAR-CIAH, Bikaner during 2020-21. The pods were blanched for different durations (3, 4, 5, 6 and 7 minutes) in boiling water to standardize blanching process. Five minutes blanching in boiling water followed by immediate dipping in cold water was found optimum for getting quality dehydrated product. Blanching treatment significantly enhanced the drying (5.67) and rehydration rate (4.65) and augmented rehydration capacity of dried pods. The dehydration recovery was 21.24% of fresh pods. The dried samples stored with HDPE pouches had low moisture content and high rehydration capacity than the samples stored with LDPE pouches. Thus, it is recommended that blanching is an essential process for quality pods. The HDPE pouches were found suitable packaging material for storage stability of dried pods.